Psychological mindedness and academic achievement of psychology students in a higher education environment - Beets, Soretha; Nienaber, Alida; Botha, Karel (University of the Free State, 2011)
This article aims to determine the relationship between psychological mindedness and academic achievement and whether there are differences in demographic variables in relation to both psychological mindedness and academic achievement. A crosssectional design was used and 211 undergraduate students participated. A biographic questionnaire as well as the psychological mindedness scale was administered and the academic records of the participants were drawn. The data were analysed by calculating correlations, t-tests and an analysis of variance. Although there is a correlation between academic achievement and psychological mindedness, other factors may also play a role in the academic achievement of undergraduate university students. Limitations and recommendations were indicated.

Die doel van hierdie studie is om die verwantskap tussen psigologiese indagtigheid en akademiese prestasie te bepaal en ook of daar verskille is in die demografiese veranderlikes in verhouding tot beide psigologiese indagtigheid en akademiese prestasie. ’n Dwarsdeursnit- ontwerp is gebruik en 211 voorgraadse studente het deelgeneem. ’n Biografiese vraelys sowel as die “psychological mindedness scale” is afgeneem, en die akademiese rekords van die deelnemers is getrek. Die data is ontleed deur die berekening van korrelasies, t-toetse en ’n analise van variansie. Alhoewel daar ‘n korrelasie tussen akademiese prestasie en psigologiese indagtigheid is, kan ander faktore ook ’n rol in die akademiese prestasie van voorgraadse studente speel. Beperkinge en aanbevelings is aangedui.
Keywords: Psychological mindedness; Academic achievement; Higher education; Undergraduate students